Comparative transcriptomics of the bovine apicomplexan parasite Theileria parva developmental stages reveals massive gene expression variation and potential vaccine antigens - Atchou, K.; Ongus, J.; Machuka, Eunice M.; Juma, John; Tiambo, Christian K.; Djikeng, Appolinaire; Silva, Joana C.; Pelle, Roger (Frontiers Media, 2020)
Theileria parva is a protozoan parasite that causes East Coast fever (ECF), an economically important disease of cattle in Africa. It is transmitted mainly by the tick Rhipicephalus appendiculatus. Research efforts to develop a subunit vaccine based on parasite neutralizing antibodies and cytotoxic T-lymphocytes have met with limited success. The molecular mechanisms underlying T. parva life cycle stages in the tick vector and bovine host are poorly understood, thus limiting progress toward an effective and efficient control of ECF. Transcriptomics has been used to identify candidate vaccine antigens or markers associated with virulence and disease pathology. Therefore, characterization of gene expression throughout the parasite's life cycle should shed light on host-pathogen interactions in ECF and identify genes underlying differences in parasite stages as well as potential, novel therapeutic targets. Recently, the first gene expression profiling of T. parva was conducted for the sporoblast, sporozoite, and schizont stages. The sporozoite is infective to cattle, whereas the schizont is the major pathogenic form of the parasite. The schizont can differentiate into piroplasm, which is infective to the tick vector. The present study was designed to extend the T. parva gene expression profiling to the piroplasm stage with reference to the schizont. Pairwise comparison revealed that 3,279 of a possible 4,084 protein coding genes were differentially expressed, with 1,623 (49%) genes upregulated and 1,656 (51%) downregulated in the piroplasm relative to the schizont. In addition, over 200 genes were stage-specific. In general, there were more molecular functions, biological processes, subcellular localizations, and pathways significantly enriched in the piroplasm than in the schizont. Using known antigens as benchmarks, we identified several new potential vaccine antigens, including TP04_0076 and TP04_0640, which were highly immunogenic in naturally T. parva-infected cattle. All the candidate vaccine antigens identified have yet to be investigated for their capacity to induce protective immune response against ECF.